Baracks. Basis of Housing Fund of Sotsgorod’s First Five-Year Plan Buildings - Grigoryevich, Meerovich Mark (ZARCH, 2015)
Sotsgorod-buildings in the period of soviet industrialization (1920-1940-ies.) often erect from scratch - in the plains, taiga or the desert. Their acquisition of workforce - was impossible without large-scale construction of the home. Barracks was the first truly mass housing being built in new buildings Sotsgorod’s in industrialization period. They provide a roof over your head about 80-90% of the population of industrial buildings. There are five identified types of barracks (the material of construction).